2020
DOI: 10.1371/journal.pone.0226736
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia limits pathogen infections through induction of host innate immune responses

Abstract: BackgroundWolbachia has been reported to suppress a variety of pathogen infections in mosquitoes, but the mechanism is undefined. Two possibilities have been proposed. One is that Wolbachia activates host immune responses, and the other one is that Wolbachia competes with pathogens for limited nutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Wolbachia contains a type 4 secretion system, which may secrete specific compounds impacting host biology and regulating the interaction between Wolbachia and other bacteria ( 47 49 ). Second, endosymbionts can induce host immune responses (such as antimicrobial peptides) which in turn may regulate bacterial diversity ( 50 52 ). Transinfected Wolbachia strains can upregulate the host's immune response ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia contains a type 4 secretion system, which may secrete specific compounds impacting host biology and regulating the interaction between Wolbachia and other bacteria ( 47 49 ). Second, endosymbionts can induce host immune responses (such as antimicrobial peptides) which in turn may regulate bacterial diversity ( 50 52 ). Transinfected Wolbachia strains can upregulate the host's immune response ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also observed a higher emergence of Wolbachia-infected offspring than that of uninfected offspring when the wasps emerged from A. pernyi eggs (Zhou et al, 2020). One potential explanation is that Wolbachia protect hosts against a broad range of pathogens by induction of host innate immune responses or competing with pathogens for nutrients (Brownlie and Johnson, 2009;Zhang et al, 2020). Some studies doubted that the abortion of Trichogramma offspring may be caused by the vertical transmitted pathogens like Nosema spp.…”
Section: Discussionmentioning
confidence: 89%
“…The study showed that the w AlbB infection in mosquitoes activates both IMD and Toll pathways and infection is maintained through maternal transmission (MT) [ 192 ]. Another study also showed that Wolbachia boosts immune responses and increase mosquitoes’ resistance to viruses, which allows the immune system to actively fight against the viruses in the arthropod host [ 193 ]. In a study series of blood-feeding mosquito trials in response to the human host, it was shown that as mosquitoes infected with w MelPop- Wolbachia strain age, they feed less compared to their uninfected counterparts as a result of the observed bent proboscis.…”
Section: Wolbachia-based Field and Experimental Studiesmentioning
confidence: 99%